Sea: Zone of Proscription and Confinement of Evils - Ribeiro, Carlos Augusto (E- Revista de Estudos Interculturais, 2021)
The sea is present in the collection of Popular Medicine collected by Michel Giacometti and published in Artes de Cura e Espanta-Males (2009). In many of the recipes and incantations belonging to various medical specialties, the sea – like the mountain or the high pine forest – is an area where evils are thrown / exorcised. From a close reading of the most explicit part of the collection regarding the relationship between the therapeutic ritual and the sea, we find that there is a clear border between humanized spaces – symptomatically, where roosters and chickens are singing and, by extension, other domesticated animals – and the so-called outlawed, non-humanized zones. Necessarily, a boundary to be veiled and maintained for the benefit of (fragile) human and non-human bodies. The person who throws the material remains of a therapeutic ritual into the sea often does so with his back to the sea. The evils are sent to the curdled, salty, sacred sea, or to the very bottom of the sea. Precisely, where they are believed to be no longer harmful and can never return. It is well known that in terms of a landscape history, the sea – as well as the mountain and the desert – was / is, because it is an area of incalculable risk and danger, a hostile landscape. And, only in modern times, the sea (as well as the seaside and the beach) is a landscape and a place of leisure. The aforementioned collection of folk medicine is a testament to this premodern mentality.